Institutional Markets, Financial Marketing, and Financial Innovation - ROSS, STEPHEN A. (Journal of Finance, 1989)
ABSTRACT Firms and institutions are monitored and controlled through a complex set of implicit and explicit contractual relations. Because of these agency theoretic relations, institutional behavior in financial markets is not a simple reflection of the preference structures of individuals. Institutional preferences give rise to a demand for new financial instruments and innovations, even when the returns on these instruments are “spanned” in the sense of complete pricing. The innovations can be thought of as solving moral hazard problems. An agency theoretic example serves to illustrate the demand, supply, and financial marketing of stripped securities. In short, institutions matter.